Line parameters of water vapor enriched by 18O from 6525 to 8011 cm−1. (September 2019) - Régalia, L.; Thomas, X.; Rennesson, T.; Mikhailenko, S.
Highlights: New spectra of water samples enriched by 18 O recorded with FTS at room temperature between 6400 and 8000 cm −1 . Retrieval of line parameters with multispectrum fitting procedure. new measurements of line positions and intensities for six water isotopologues (H2 16 O, H2 17 O, H2 18 O, HD 16 O, HD 17 O, and HD 18 O). Abstract: This study is a continuation of experimental efforts on the analysis of the near-infrared absorption spectrum of water vapor. Our previous studies were focused on water vapor in natural isotopic abundance. Now we are interested in the H2 18 O water isotopologue. New spectra of water samples enriched by 18 O were recorded between 6400 and 9400 cm −1 in Reims with the Connes-type Fourier Transform Spectrometer, built in our laboratory. The spectra were recorded at room temperature with a H2 18 O abundance enrichment of about 95% and a non apodized resolution of 0.010 cm −1 . Pressure varied from 2 to 13 torr and the absorption path length was from 67 cm to 1001 m. This article presents the results of the analysis of the first part of the whole recorded spectral range below 8000 cm −1 . About 8100 absorption lines were found in the recorded spectra with an absorption path length from 8 to 88 m between 6525 and 8011 cm −1 . Overall, 7993 lines were assigned to 8647 transitions of six water isotopologues (H2 16 O, H2 17 O, H2 18 O, HD 16 O, HD 17 O, and HD 18 O). Ninety-eight lines with intensity values between 6 × 10 −27 and 1.45 × 10 −25 cm/molecule were left unassigned. More than 870 H2 18 O, H2 17 O and HD 18 O lines were observed for the first time. The observed line positions allow to obtain about 90 new or corrected rotation-vibration energy levels of H2 18 O and H2 17 O. Comparison of line positions and intensities with literature data are presented and discussed. Some examples of disagreements between the measurements and data from the literature are presented in the last part of this article.